Justice ; Misunderstood malady ; The Storyteller [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
A case of Justice Gutierrez on graft and corruption. A report on epilepsy, a recurrent seizure often mistaken a psychiatric illness. A mobile library set up by NEDA Director General Cielito Habito and his wife to the poor children in Laguna.